2013
DOI: 10.1371/journal.pone.0075171
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcome of Pneumonia Caused by Methicillin-Resistant Staphylococcus aureus (MRSA) in Canadian Hospitals

Abstract: BackgroundMRSA remains a leading cause of hospital-acquired (HAP) and healthcare-associated pneumonia (HCAP). We describe the epidemiology and outcome of MRSA pneumonia in Canadian hospitals, and identify factors contributing to mortality.MethodsProspective surveillance for MRSA pneumonia in adults was done for one year (2011) in 11 Canadian hospitals. Standard criteria for MRSA HAP, HCAP, ventilator-associated pneumonia (VAP), and community-acquired pneumonia (CAP) were used to identify cases. MRSA isolates u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…26 Methicillin-resistant S. aureus (MRSA) is among the most frequently identified pathogens causing healthcare-associated pneumonia (HCAP), HAP, and VAP worldwide. 33 Although it appears to be a relatively uncommon cause of CAP, 34 MRSA may be an important emerging respiratory pathogen in the community, associated with severe necrotizing infection especially following recent influenza. 35 …”
Section: Etiologymentioning
confidence: 99%
“…26 Methicillin-resistant S. aureus (MRSA) is among the most frequently identified pathogens causing healthcare-associated pneumonia (HCAP), HAP, and VAP worldwide. 33 Although it appears to be a relatively uncommon cause of CAP, 34 MRSA may be an important emerging respiratory pathogen in the community, associated with severe necrotizing infection especially following recent influenza. 35 …”
Section: Etiologymentioning
confidence: 99%
“…3 In terms of the impact of specific organ system failure on VAP outcomes, Gursel et al described a 38% incidence of acute renal failure (ARF) in this patient population. 16 High APACHE scores, MDRO and sepsis were independent risk factors for development of ARF during VAP episodes in that series.…”
Section: Discussionmentioning
confidence: 99%
“…2 Amongst MDRO, methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a significant etiologic agent in nosocomial infections worldwide. 3 MRSA has been reported as a common cause of VAP, along with Enterobacteriaceae (usually the most common cause) and Pseudomonas aeruginosa in several series. [3][4][5] In this context, it is important to better understand the determinants of clinical failure in VAP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO found that national data obtained for E. coli, K. pneumoniae and S. aureus showed that the proportion resistant to commonly used antibacterial drugs exceeded 50% in many settings [4]. It is associated with high morbidity and mortality [31,32]. One study found in the wars of Iraq and Afghanistan cases of infection were predominantly due to multi-drug resistant pathogens, likely acquired within the military healthcare system [33].…”
Section: The Futurementioning
confidence: 99%